Upper Face: Clinical Anatomy and Regional Approaches with Injectable Fillers. (November 2015) - Sykes, Jonathan M.; Cotofana, Sebastian; Trevidic, Patrick; Solish, Nowell; Carruthers, Jean; Carruthers, Alastair; Moradi, Amir; Swift, Arthur; Massry, Guy G.; Lambros, Val; Remington, B. Kent
Abstract : Background: The use of facial fillers has been rapidly increased as the range of injectable products and indications continues to expand. Complications may arise from improper placement or technique. This article highlights the importance of anatomic knowledge when using injectable fillers in the face. Methods: A detailed review of the clinical anatomy of the upper face is performed. Regional approaches are described using the applied anatomy to efficiently and safely augment the different subunits of the upper face. Results: Key aspects of safe and successful injection of fillers in the upper face include a thorough knowledge of the location of fat compartments and neurovascular structures. Awareness of these structures enables the practitioner to maximize injections, while avoiding damage to important nerves and vessels. Conclusion: A detailed knowledge of the anatomy and properties of the product is paramount to maximize the efficacy while minimizing the risk of complications. Abstract : Supplemental Digital Content is available in the text.